J2EE (Java 2 Enterprise Edition) - Griffith, Arthur; Virtual Training Company ([Australia] : Virtual Training Company, 2008)
The J2EE software includes development and deployment systems for Java Servlets and Java Serverpages. Both of these combine Java and HTML to produce web pages on demand. VTC author Arthur Griffith takes a step by step guide to understanding this powerful component of Java programming
Title from container
Trainig CD
Contains 75 movies with total time 6 hours
System requirements: Mac: System 9 or higher ; PC: Windows 98 or higher, 32MB System RAM, 6MB Video RAM, 16x CD-ROM ; QuickTime 6
Keywords: Java (Computer program language); Web site development; Application software -- Development